PERLINDUNGAN HUKUM TERHADAP DEBITUR YANG MEMPEROLEH FASILITAS KREDIT SEPEDA MOTOR DENGAN PERJANJIAN FIDUSIA - Noor, Erma Zahro (Jurnal Panorama Hukum, 2017)
In Indonesia there are two financial institutions that always provide credit facilities to the people who needs funds, that financial institutions are in the form of bank and non bank or so-called LKBB, where one form is a financial institution (leasing).In conducting the financing agreement for the purchase of motor vehicles on credit to the consumer (debtor), that financial institutions (leasing) are always poured in the form of standard contracts which must be approved by the customer (debtor), despite clause (contents of) the agreement is more likely to benefit the institution financing (creditor) and complicate/ensnare even tend to harm the consumer (debtor), because the consumer has always been on the weaker side and do not have the strength to fight for their rights against the treaty that already signed.. As a reference to unify the differences that arise in the resolution of problem loans in financial institutions, can use the rules as stipulated in Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution and as an umbrella law to protect consumers as the debtor can use the rule-rules contained in Law No. 8 of 1999 on consumer protection.